A new alien species in the Mediterranean? On the presence of Sirpus monodi Gordon, 1953 (Brachyura, Pirimelidae) in Greece - PANCUCCI-PAPADOPOULOU, M.A.; NALETAKI, M. (Mediterranean Marine Science, 2007)
Sirpus monodi, first described from West Africa (Dakar, Senegal) and later reported from Mauritania and Congo, has now been found in the eastern Mediterranean. This work reports on its occurrence in two Greek localities.